LncRNA H19 Influences Cellular Activities via the miR-454-3p/BHLHE40 Axis in Anaplastic Thyroid Carcinoma - Wu, Yang; Yang, Jihua; Zhang, Honglai; Cheng, Jingjing; Lei, Peijie; Huang, Jianyuan (Hormone and Metabolic Research, 2023)
Anaplastic thyroid carcinoma (ATC) is an aggressive malignancy threatening patients’ life quality. Our previous study has demonstrated that inhibition of long non-coding RNA H19 (lncRNA h19; H19) blocks ATC growth and metastasis. The current study aimed to further explore the potential mechanism of H19 in ATC. Expression of H19, miR-454-3p, and BHLHE40 mRNA was measured using RT-qPCR in tissue samples and cell lines. The dual-luciferase reporter assay and Pearson correlation analysis were used to explore the interaction among H19, miR-454-3p, and BHLHE40. The biological process of proliferation, migration, and invasion was determined using loss- or gain-function CCK-8 and Transwell assays. Western blot assay was used to evaluate the changes in protein levels. H19 was elevated in ATC tissues and cell lines. Based on online prediction database results, miR-454-3p might be a target of H19, and BHLHE40 might be a direct target of miR-454-3p. miR-454-3p expression was decreased in ATC and had a negative interaction with H19. BHLHE40 mRNA expression was increased and has a negative correlation with miR-454-3p and a positive correlation with H19. Downregulation of miR-454-3p and upregulation of BHLHE40 could reverse the decreased cellular activities caused by si-H19. Moreover, the silence of H19 modulates BHLHE40 to affect the PI3K/AKT protein levels and apoptotic-related protein levels. The current study provided a potential detailed mechanism of H19 in ATC, and lncRNA H19-miR-454-3p-BHLHE40 interaction may be a new experimental basis for prognosis and targeted therapy for ATC patients.
Keywords: anaplastic thyroid carcinoma; progression; prognosis; PI3K/AKT; H19